Use of proton pump inhibitors: An exploration of awareness, attitude and behavior of health care professionals of Riyadh, Saudi Arabia - Syed Mohammed Basheeruddin Asdaq; Marah ALbasha; Asmaa Almutairi; Reham Alyabisi; Alaa Almuhaisni; Roaa Faqihi; Abdulhakeem S. Alamri; Walaa F. Alsanie; Majid Alhomrani (Elsevier, 2021)
Background & Objectives: One of the broadly talked about class of medications for their extravagantly expanded abuse is proton pump inhibitors (PPIs). In spite of the fact that, they are known to be profoundly useful, it is accounted for several adverse manifestations. Health care professionals can assume an essential part in controlling its irrational use. The purpose of this study was to explore the knowledge, attitude and behavior of health care professionals of Riyadh region of Saudi Arabia on the use of PPIs by a cross-sectional study design. Methods: The study data was obtained through a validated self-administered questionnaire covering knowledge (20 items), attitude (8 items) and behavior (6 items). Furthermore, demographic questions were placed to decide their effect on the intended three domains. The results were analysed by descriptive analysis and affirmed by multinomial regression method using SPSS-IBM 25. Results: Of 414 surveyors, 121 (31%), 182 (44%) and 103 (25%) were doctors, pharmacist and nurses, respectively. Average age of participants' was 33.96 ± 8.37 years. Both doctors and pharmacist showed better degree of information (13.17/20 and 13.25/20) and good attitude (6.66/8 and 6.9/8) towards PPI use compared to nurses. Altogether higher extent of knowledge score showed by highly educated individuals, middle age groups and those with more practicing experience. The reliance on the utilization of PPI is less among pharmacist and nurses when compared to doctors. The outcome of the regression analysis exhibited that the odds of having low knowledge is more in young and bachelor degree holders. Interpretation & Conclusion: Healthcare professionals in the Riyadh area are generally positive about the use of PPIs. However, increasing their level of knowledge and reducing their reliance on PPIs must be strengthened. Frequent professional development programs and trainings for healthcare professionals are needed to minimize widespread PPI overuse.